Comparison of the Structures of SEIR and SVEIL Mathematical Models of Tuberculosis - Takal, Mohammad Hanif; Noori, Noorullah; Baidar, Abdul Wakil (Journal of Natural Sciences – Kabul University, 2025)
Mathematical models of diseases, which study the mechanisms of disease transmission and control from a mathematical perspective, play a significant role in assisting public health policymakers in designing strategies for disease control. In this paper, two mathematical models of tuberculosis, SEIR and SVEIL, are analyzed and compared. Various aspects of the models, such as their structure, stability analysis, basic reproduction number, differences in variables and parameters, and scope of application, are evaluated. We demonstrated that the SVEIL model is more comprehensive than the SEIR model; it incorporates vaccination and successful treatment, and the loss of immunity against the disease, offering a more realistic analysis of disease dynamics. However, due to its expanded structure, the SVEIL model involves greater computational complexity in conducting stability analysis and calculating the basic reproduction number.